Effects of the Particle Shape and Size on the Single-Particle Breakage Strength. (1st December 2022) - Qing, Yun; Qiu, Zhenfeng; Tang, Yi; Deng, Wenjie; Zhang, Xujin; Miu, Jilun; Song, Shaoxian
Abstract : The strength and deformation of a soil foundation are related to the strength of each particle. Maybe the shape affects the strength of a particle. In this study, single-particle breakage tests were conducted on limestone particles of different sizes to analyze the influence of limestone particle shapes on the particle crushing strength. The results showed that 90 percent of limestone particle shapes were oblate spherical, subspherical, and long spherical particles randomly selected from the soil foundation. The single-particle breakage test results showed that the characteristic stress of limestone particles increases with the increased particle size. The crushing strength of limestone particles increased with the increase in particle size. There was a significant size effect on the single-particle compressive strength. The relationship between the characteristic strength and the particle size can be fitted by a power exponential formulation of four types of limestone particle shapes. The more irregular the particle shape, the smaller the Weibull modulus ( m ) and the power index and the more obvious the particle strength size effect.